2009
DOI: 10.1080/15412550903140881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluticasone Propionate/Salmeterol (250/50) on COPD Exacerbations and Impact on Patient Outcomes

Abstract: Prevention and treatment of COPD exacerbations are recognized as key goals in disease management. This randomized, double-blind, parallel-group, multicenter study evaluated the effect of fluticasone propionate/salmeterol 250 mcg/50 mcg (FSC 250/50) and salmeterol 50 mcg (SAL) twice-daily on moderate/severe exacerbations. Subjects received treatment with FSC 250/50 during a one month run-in, followed by randomization to FSC 250/50 or SAL for 52 weeks. Moderate/severe exacerbations were defined as worsening symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 21 publications
9
134
1
7
Order By: Relevance
“…Although MAIT cells may not be required for defense against monomicrobial infections with S. pneumoniae, a deficiency of MAIT cells in nonstreptococcal bacterial sepsis has been described in the intensive care setting, and is associated with increased acquisition of nosocomial infections (47). Thus, our findings may begin to provide an explanation for the increased risk of pneumonia associated with ICS use in COPD (13)(14)(15)(16)(17)(18). In addition, although NTHi is a commensal of the upper respiratory tract, it is not present as a persistent, distinct microbial community in the lower respiratory tract in health.…”
Section: Cd161mentioning
confidence: 70%
See 1 more Smart Citation
“…Although MAIT cells may not be required for defense against monomicrobial infections with S. pneumoniae, a deficiency of MAIT cells in nonstreptococcal bacterial sepsis has been described in the intensive care setting, and is associated with increased acquisition of nosocomial infections (47). Thus, our findings may begin to provide an explanation for the increased risk of pneumonia associated with ICS use in COPD (13)(14)(15)(16)(17)(18). In addition, although NTHi is a commensal of the upper respiratory tract, it is not present as a persistent, distinct microbial community in the lower respiratory tract in health.…”
Section: Cd161mentioning
confidence: 70%
“…However, effects of ICS are modest and likely restricted to certain subgroups of this heterogeneous condition (3) whereas evidence is accumulating from well-designed clinical trials that ICS increase the incidence of community-acquired pneumonia (13)(14)(15)(16)(17)(18). The mechanisms underlying this effect remain unknown, and have been highlighted as a research priority (3).…”
mentioning
confidence: 99%
“…(17) In patients with moderate or severe COPD, as determined by the GOLD classification, the use of salmeterol in combination with fluticasone was shown to be superior to the use of SABAs in combination with SAMAs, (18) as well as to the use of salmeterol in isolation. (19)(20)(21) In patients with severe or very severe COPD, as determined by the GOLD classification, there were no differences between the salmeterol-fluticasone and formoterolbudesonide combinations in terms of symptom The process of selection allowed us to include 84 original articles in the present review. Many of those articles addressed more than one class of medication and various outcomes, which generated 420 analyses.…”
Section: Article Selectionmentioning
confidence: 99%
“…Donohue et al (16) found no significant differences between patients treated with formoterol and those treated with salmeterol regarding the number of exacerbations occurring in one year. In the analyses evaluated, the use of LABAs and ICs in combination was shown to be superior to that of LABAs or ICs in isolation for the following outcome measures (19)(20)(21)43,47) : number of exacerbations; severe exacerbations requiring hospitalization; and use of systemic corticosteroids.…”
Section: Exacerbationmentioning
confidence: 99%
See 1 more Smart Citation